2018
DOI: 10.3390/cancers10020041
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Sox2 at Threonine 116 is a Potential Marker to Identify a Subset of Breast Cancer Cells with High Tumorigenecity and Stem-Like Features

Abstract: We have previously identified a novel phenotypic dichotomy in breast cancer (BC) based on the response to a SRR2 (Sox2 regulatory region 2) reporter, with reporter responsive (RR) cells being more tumorigenic/stem-like than reporter unresponsive (RU) cells. Since the expression level of Sox2 is comparable between the two cell subsets, we hypothesized that post-translational modifications of Sox2 contribute to their differential reporter response and phenotypic differences. By liquid chromatography-mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Our pooled data suggested that SOX2 expression was not correlated with ER status, PR status, and TN status of breast cancer, which were consistent with the previous studies regarding the correlation between SOX2 expression and ER status [23, 24, 26, 31, 34, 36, 38], PR status [23, 24, 26, 31, 36, 39], and TN status [24, 26, 31, 34, 36, 38]. Some studies reported that SOX2 expression was related to HER2 status [26] and EGFR status [30].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our pooled data suggested that SOX2 expression was not correlated with ER status, PR status, and TN status of breast cancer, which were consistent with the previous studies regarding the correlation between SOX2 expression and ER status [23, 24, 26, 31, 34, 36, 38], PR status [23, 24, 26, 31, 36, 39], and TN status [24, 26, 31, 34, 36, 38]. Some studies reported that SOX2 expression was related to HER2 status [26] and EGFR status [30].…”
Section: Discussionsupporting
confidence: 91%
“…No significant relationship was observed between SOX2 expression and lymph node metastasis and lymphovascular invasion of patients with breast cancer, which was consistent with the previous publications regarding SOX2 expression with lymph node metastasis [20, 23, 24, 31, 36, 37, 38, 41] and lymphovascular invasion [20, 24, 31, 36]. Some previous publications reported that SOX2 expression was positively linked to tumor grade [5, 20, 21, 23, 24, 32, 33, 36, 38, 39, 41], clinical stage [22, 32, 38], and pT stage [20, 23, 30], which were consistent with our results that showed that SOX2 expression was associated with advanced tumor grade, clinical stage, and pT stage. This suggests that SOX2 expression plays an important role in the progression of breast cancer.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations